EXTRAMAMMARY PAGET'S DISEASE WITH METHOTREXATE THERAPY: A CASE REPORT - Anggreini Oktavia Trisno; Cindy Christella Chandra; Sukmawati Tansil Tan (The International Journal of Medical Science and Health Research, 2026)
Introduction: Extramammary Paget's Disease (EMPD) is an uncommon intraepidermal adenocarcinoma that develops in regions containing apocrine glands, including the scrotum, inguinal folds, and perineum. It is most frequently observed in older adults and is often initially mistaken for benign conditions such as dermatitis or fungal infections due to its vague clinical appearance. Case Report: A 67-year-old man presented with a one-year history of erythematous, pruritic, and painful lesions located in the right groin and scrotal area. Physical examination revealed an erythematous patch with hyperpigmented macules, accompanied by erosion, scaling, and a plaque-like kissing lesion. Histopathological analysis confirmed the presence of characteristic Paget cells within the epidermis, leading to a definitive diagnosis of EMPD. The patient received therapy with topical methotrexate combined with topical gentamicin. Discussion: Diagnosing EMPD is challenging because its clinical features mimic those of common inflammatory skin disorders. Histopathology remains the diagnostic gold standard. Although surgical excision is the conventional treatment, topical methotrexate represents a promising non-invasive alternative, especially for limited disease or when surgery is not feasible. In the present case, marked clinical improvement was noted after four weeks of treatment, including reduced erythema and erosion, along with complete resolution of pruritus and pain. Conclusion: The combination of topical methotrexate and gentamicin produced favorable clinical results in this elderly patient with EMPD. This case supports the potential role of topical methotrexate as a safe, cost-effective, and well-tolerated therapeutic option for selected individuals with EMPD.